Lessons learnt from the recent EURADOS intercomparisons in computational dosimetry. (August 2022) - Rabus, Hans; Zankl, Maria; Gómez-Ros, José Maria; Villagrasa, Carmen; Eakins, Jonathan; Huet, Christelle; Brkić, Hrvoje; Tanner, Rick
Abstract: Organized by Working Group 6 "Computational Dosimetry" of the European Radiation Dosimetry Group (EURADOS), a group of intercomparison exercises was conducted in which participants were asked to solve predefined problems in computational dosimetry. The results of these comparisons were published in a series of articles in this virtual special issue of Radiation Measurements. This paper reviews the experience gained from the various exercises and highlights the resulting conclusions for future exercises, as well as regarding the state of the art and the need for development in terms of quality assurance for computational dosimetry techniques.